Factors influencing the intention to commit unethical behaviour among youth in Pahang - Tengku Intan Nabilah, Tenku Sulaiman; Fatimah, Mahmud; Hasnah, Haron; Fuadah, Johari; Suhaili, Jalil; Zalailah, Salleh (Universiti Malaysia Pahang, 2023)
Integrity refers to the qualities that exist in everyone based on the and high moral practices. Therefore, youth as the catalyst of the nation, need to be ethical in their actions and make ethical values as a culture in their daily lives. Recognizing the importance of integrity, this study is expected to help the public sector mainly in pahang plan strategies to instill the culture of integrity among youth. Thus, the main objective of this study is to identify the factors that influence the intention to commit unethical behavior among youth in Pahang. The objective of the study is to examine whether attitudes (love of money and greed), subjective norms (parental influence and peer influence) and perceived behavioral control (financial stress and capability) and religiosity will have a relationship with Intention to commit unethical behaviour . The study was conducted using a survey. A total of 148 respondents who are youths between the ages of 18 to 40 who work in government agencies participated the results of this study revealed that religiosity shows a significant and negative relationship with intention to commit unethical behaviour. This study adds to the body of knowledge about intention to commit unethical behavior. It is intended that this study would improve awareness of youth in ensuring that they are able to perform their duties with integrity.